Modeling of Concrete-Frozen Soil Interface from Direct Shear Test Results - Meng Xiong; Pengfei He; Yanhu Mu; Xinlei Na (Advances in Civil Engineering)
The shear behaviors of concrete-frozen soil interface are important for analyzing the performance of engineering structures buried in the frozen ground. In this paper, a series of direct shear tests were carried out to determine the concrete-soil interface behaviors at different test temperatures (19°C, −1°C, −3°C, and −5°C) and initial water contents (9.2%, 13.1%, 17.1%, and 20.8%) of soils. The interface shear behaviors, including the shear stress versus horizontal displacement, interface cohesion, and interface friction coefficient, were analyzed based on the test results. Then, a simple, nonlinear model was proposed and verified for the interface shear behaviors. The results show that the effect of initial water content and test temperature on the interface shear behavior is significant, and the peak stress increases with the increasing initial water content and decreasing test temperature. The interface cohesion is sensitive to the test temperature and initial water content, while the interface friction coefficient is insensitive to both the factors. The parameters of the simple nonlinear model can be gained by back-analyzing the test results. The predictions made by the proposed model are found to be in good agreement with the experimental results.